2019
DOI: 10.1111/tpj.14185
|View full text |Cite
|
Sign up to set email alerts
|

A dissection model for mapping complex traits

Abstract: Summary Many quantitative traits are composites of other traits that contribute differentially to genetic variation. Quantitative trait locus (QTL) mapping of these composite traits can benefit by incorporating the mechanistic process of how their formation is mediated by the underlying components. We propose a dissection model by which to map these interconnected components traits under a joint likelihood setting. The model can test how a composite trait is determined by pleiotropic QTLs for its component tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…However, as have been shown above, the characterization of dependent effects is not dependent on sample size but on net genetic effect curves. The estimation of main genetic effect curves does rely on sample size, but both simulation and experimental studies suggest that a sample size of 100 to 400 can reasonably well estimate such curves if the number of time points is two or more times the number of curve parameters 97 , 98 . Furthermore, traditionally defined epistasis is the genetic interaction between different loci, without knowing the direction and sign of epistasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as have been shown above, the characterization of dependent effects is not dependent on sample size but on net genetic effect curves. The estimation of main genetic effect curves does rely on sample size, but both simulation and experimental studies suggest that a sample size of 100 to 400 can reasonably well estimate such curves if the number of time points is two or more times the number of curve parameters 97 , 98 . Furthermore, traditionally defined epistasis is the genetic interaction between different loci, without knowing the direction and sign of epistasis.…”
Section: Discussionmentioning
confidence: 99%
“…FunMap is a statistical model, proven to be powerful for mapping growth traits by integrating biologically meaningful growth equations 97 , 108 – 110 . More recently, Sang et al 98 . have extended FunMap to coFunMap designed to map a composite trait mathematically constituted by different traits.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Simulation studies based on fitting parametric models have demonstrated that integrating longitudinal measures of phenotypes in a single population can provide increased resolution and power to identify quantitative trait loci 16 . Here we employed nonparametric models which required fewer initial assumptions about the pattern of how phenotypes change over time 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Plant growth and development is a dynamic process, responding to environmental perturbations and regulated by different suites of genes at different times and in different environments 4,[10][11][12][13][14][15] . The availability and use of time-series trait data from mapping and association populations has the potential to increase both the accuracy and power of gene mapping studies 4,16 . It may also provide greater insight into the biologically distinct roles different loci pay in determining final phenotypes.…”
Section: Introductionmentioning
confidence: 99%